Estudos de propriedades termodinâmicas e estruturais dos líquidos etilenoglicol e glicerol utilizando simulação computacional - Arruda Sobrinho, Aparecido de (Universidade Federal de São Carlos, 2003)
Ethylene glycol and glycerol are molecular liquids with many internal degrees of freedom. Rotations along specific chemical bonds allow the formation of intramolecular hydrogen bonding, leading to several stable conformational possibilities. Due to the capability of these liquids to form one or more hydrogen bonding with appropriate solutes, they have been used to verify the influences of these bonds in the conformational and thermodynamics properties of molecules. The studies were performed using Molecular Dynamics methodology implemented in the TINKER package. A combination of the force fields OPLS-AA (Optimized Potential for Liquid Simulations-All Atoms) and AMBER was used to represent molecular interactions. Structural and thermodynamic properties of liquid ethylene glycol in the ensemble NpT at temperatures of 265 K, 300 K, 350 K and 465 K and 1.0 atm were calculated. The same study was performed for glycerol at temperatures of 300 K, 400 K and 555 K. Internal rotations along all axes defined by bonds C-O and C-C had been considered. The formation and behavior of hydrogen bonds was as a function of time were particularly considered.
Keywords: Química - teoria; Termodinâmica; Química simulação computacional; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::QUIMICA TEORICA